Predator density influences nest attendance of Yellow‐headed Blackbirds Xanthocephalus xanthocephalus. (1st February 2019) - Behrens, Colby; Ruff, Zachary J.; Harms, Tyler M.; Dinsmore, Stephen J.
Abstract : Nest attendance behaviour in birds is a function of the careful balance between the risk of nest predation and the needs of the parents and nestlings. This attendance must be carefully regulated, as increased parental activity at the nest increases nest predation risk. We tested the long‐standing hypothesis that nest predation risk influences parental behaviour by evaluating the influence of local Marsh Wren Cistothorus palustris density on the off‐bout frequency of Yellow‐headed Blackbirds Xanthocephalus xanthocephalus . Marsh Wren density was negatively correlated with Yellow‐headed Blackbird off‐bout frequency during the morning (05:00–10:00 h) and evening (16:00–21:00 h), suggesting that Yellow‐headed Blackbirds alter their nest attendance behaviour in response to a perceived increased risk of nest predation. We suggest that Yellow‐headed Blackbirds are sensitive to nest predation risk and alter their behaviour accordingly to increase overall fitness, although future research is needed to evaluate the influence of Marsh Wren nest predation on the reproductive success of Yellow‐headed Blackbirds.